Discourse Coherence as a Cue to Reference in Word Learning: Evidence for Discourse Bootstrapping. Issue 1 (7th January 2019) - Sullivan, Jessica; Boucher, Juliana; Kiefer, Reina J.; Williams, Katherine; Barner, David
Abstract: Word learning depends critically on the use of linguistic context to constrain the likely meanings of words. However, the mechanisms by which children infer word meaning from linguistic context are still poorly understood. In this study, we asked whether adults ( n = 58) and 2‐ to 6‐year‐old children ( n = 180) use discourse coherence relations (i.e., the meaningful relationships between elements within a discourse) to constrain their interpretation of novel words. Specifically, we showed participants videos of novel animals exchanging objects. These videos were accompanied by a linguistic description of the events in which we manipulated a single word within a sentence ( and vs. because ) in order to alter the causal and temporal relations between the events in the discourse (e.g., "One animal handed the baby to the other animal [and/because] the baby started crying in the talfa 's arms"). We then asked participants which animal (the giver or the receiver) was the referent of the novel word. Across two experiments, we found evidence that young children used the causal and temporal relations in each discourse to constrain their interpretations of novel words.